Video Compression Schemes Using Edge Feature on Wireless Video Sensor Networks. (21st October 2012) - Nguyen Huu, Phat; Tran-Quang, Vinh; Miyoshi, Takumi
Abstract : This paper puts forward a low-complexity video compression algorithm that uses the edges of objects in the frames to estimate and compensate for motion. Based on the proposed algorithm, two schemes that balance energy consumption among nodes in a cluster on a wireless video sensor network (WVSN) are proposed. In these schemes, we divide the compression process into several small processing components, which are then distributed to multiple nodes along a path from a source node to a cluster head in a cluster. We conduct extensive computational simulations to examine the truth of our method and find that the proposed schemes not only balance energy consumption of sensor nodes by sharing of the processing tasks but also improve the quality of decoding video by using edges of objects in the frames.